Prefabricated Reinforcement in Construction Using VDC: Case Study Ovalo Monitor Bridge - Tuesta Schuler, Rodrigo (2024)
In construction projects, there may be rework and delays associated with construction processes with a low level of industrialization, resulting from the lack of constructability of the designs. To promote industrialization and improve the project's constructability, we implemented the Virtual Design & Construction (VDC) methodology, combined with a system of prefabricated reinforcement cages (PRC) elements in constructing an 870- meter span bridge located in Lima, Peru. The objective was to reduce structural rebars' assembly times, replace the traditional on-site processes of cutting, bending, and assembling steel with an industrial process based on systems of PRC steel elements. As a result, the assembly times of the structural item were reduced by 31%, thanks to the use of PRC elements. In addition, due to the VDC methodology, a 100% buildable design of the PRC elements was achieved.